Cyanobacterial biological nitrogen fixation as a sustainable nitrogen fertilizer for the production of microalgal oil - Do Nascimento, Mauro (2015)
Oleaginous microalgae have a great potential as a feedstock for biodiesel and other biofuels. However, the current cost of producing biofuels from microalgae biomass is still high to envision massive and profitable commercialization in the near future. One of the drawbacks of implementing large-scale cultivation of these organisms is the unsustainable requirement of N-fertilizers. It is presumed that co-production of higher value by-products in the frame of a biorefinery would increase the profitability of producing oil from microalgae. The aim of this work is to provide proof-of-concept for the complete substitution of chemical N-fertilization by on-site biological N2 fixation in a process of microalgal oil production. We show the efficient conversion of biomass of a N2-fixing cyanobacterium into oil-rich microalgae biomass when the eukaryotic alga is fed with a cyanobacterium extract as a sole source of nutrients. Oil production yields in environmental photobioreactor simulations were in the range of current yields obtained at the expense of synthetic N-fertilizer and up to 20-fold higher than those reported when using plant feedstocks.